Potential Risk of Calcified Nanoparticles for Recurrent Urinary Tract Infection after Minimally Invasive Percutaneous Nephrolithotomy for Renal Calculi: Calcified Nanoparticles for Recurrent Urinary Tract Infection - Hu, Xiaojian; Dang, Xiaoping; Shi, Tong; Niu, Bin; Zhang, Qiong; Zheng, Liang; Ni, Feng (Cellular and Molecular Biology, 2022)
Among urolithiasis, urolithiasis is a more extensive and difficult to treat disease. In recent years, with the development of endoscopic equipment and related surgical methods, a new treatment, namely minimally invasive percutaneous nephrolithotomy, appears and is widely used in the treatment of renal calculi. It has been developed for more than 50 years since its appearance. Its advantages are a high stone clearance rate, small surgical trauma, fewer intraoperative and postoperative complications, and a short recovery time for postoperative patients. It is widely used in clinical treatment. The purpose of this paper is to study the potential risk factors of recurrence and the possibility of urinary tract infection in patients with renal calculi after minimally invasive percutaneous nephrolithotomy (MPCNL) with calcified nanoparticles, so as to obtain correct nursing knowledge and reduce recurrence and infection. In order to explore the renal calculi caused by calcified nanoparticles (CNPs), we established a rat model of renal calculi, injected CNPs into rats, collected experimental samples after a specified time, and determined NGAL, OPN and MCP-1 by enzyme-linked immunosorbent assay (ELISA) and compared them with the formation of crystallization. In the study of the possible influencing factors of septic shock after PCNL, we established a multivariate regression analysis and model, used statistical methods and professional statistical software, and used the method of classified data analysis to find out the influencing factors. After the experiment, we found that positive urine culture (P < 0.05) and preoperative urinary tract infection (P < 0.05) were significant influencing factors, and the total accuracy was 99.2%. At the same time, it is concluded that calcium nanoparticles can promote the retention, adhesion and aggregation of calcium salt crystals in the kidney, and then lead to the formation of stones.